(untitled) (Chicago, Ill., 2013)
Features the grandeurs of Yosemite National Park, plus mountains, volcanoes, and Alaskan wonders in nineteen other parks.
Keywords: Công viên quốc gia và khu bảo tồn,National parks and reserves; Hoa Kỳ,United States